Moringa oleifera-based feed supplement protects against renal ischaemia/reperfusion injury via downregulation of Bax/caspase 3 signaling - Afolabi, Oladele A.; Akhigbe, Tunmise M.; Hammed, Sodiq. O.; Hamed, Moses A.; Ekundina, Victor O.; Ajike, Richard A.; Alabi, Babatunde A.; Akhigbe, Roland E. (Frontiers in Nutrition, 2024)
Introduction Ischaemia/reperfusion (I/R) may lead to acute kidney injury via the induction of oxidative stress. On the other hand, Moringa oleifera has been reported to exert antioxidant activities. This study was designed to assess whether or not Moringa oleifera-based feed supplement could prevent I/R-induced renal injury. Materials and methods Renal I/R was induced by occluding the right renal artery for 30 min followed by a 2-h reperfusion. Results Renal I/R led to increased absolute renal weight and renal organo-somatic weight index. Renal I/R also caused distortion of renal histoarchitecture and impaired renal function evidenced by elevated serum creatinine and blood urea nitrogen. In addition, renal I/R significantly elevated renal levels of hydrogen peroxide, MDA, and advanced oxidation protein products, but suppressed the levels of reduced glutathione, protein thiol, and non-protein thiol, and the activities of superoxide dismutase and glutathione peroxidase. In addition, renal I/R up-regulated myeloperoxidase activity and the renal levels of NO, TNF-α, and IL-6. Renal I/R also up-regulated Bax and caspase 3 expression in the kidney. Furthermore, I/R-driven structural and biochemical alterations were markedly inhibited by Moringa oleifera-based feed supplement. Discussion These results suggest that Moringa oleifera-based feed supplement may preserve the gross and histoarchitectural integrity of the kidney as well as renal function via downregulation of Bax/caspase 3 signaling by targeting oxidative stress, inflammation and apoptosis in the kidney of I/R rat.